BDNF protects against stress-induced impairments in spatial learning and memory and LTP - Radecki, Daniel T.; Brown, Laurie M.; Martinez, James; Teyler, Timothy J. (Hippocampus, 2005)
The present study investigated whether infusion of brain‐derived neurotrophic factor (BDNF) could ameliorate stress‐induced impairments in spatial learning and memory as well as hippocampal long‐term potentiation (LTP) of rats. Chronic immobilization stress (2 h/day × 7 days) significantly impaired spatial performance in the Morris water maze, elevated plasma corticosterone, and attenuated LTP in hippocampal slices from these animals as compared with normal control subjects. BDNF was infused into the left hippocampus (0.5 μl/h) for 14 days, beginning 7 days before the stress exposure. The BDNF group was protected from the deleterious effects of stress and performed at a level indistinguishable from normal control animals despite the presence of elevated corticosterone. BDNF alone and sham infusions had no effect on performance or LTP. These results demonstrate that spatial learning and memory, and LTP, a candidate neural substrate of learning and memory, are compromised during chronic stress, and may be protected by BDNF administration. © 2004 Wiley‐Liss, Inc.